2013
DOI: 10.1080/13811118.2013.776439
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Deliberate Self-Harm and Coping in Adolescents: A Critical Review of the Last 10 Years' Literature

Abstract: Coping is commonly associated with deliberate self-harm (DSH) in adolescents. This article reviews the published literature from 2000 to 2010, aiming to highlight the current evidence supporting this association. Eighteen studies met the inclusion criteria, a total sample of 24,702 subjects was obtained and 17% were DSH cases. Emotion-focused coping style and in particular avoidant coping strategies have consistently been associated with DSH in adolescents. Problem-focused coping style seems to have a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 39 publications
(146 reference statements)
8
43
1
3
Order By: Relevance
“…These findings are in agreement with several studies (Kirchner, Ferrer, Forns, & Zanini, ; Manca, Presaghi, & Cerutti, ) and the results of the systematic review by Guerreiro et al. (), who concluded that emotion‐focused and avoidance strategies were consistently linked with self‐harming behavior. The perception of parental support is an important protection factor for NSSI (Baetens et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with several studies (Kirchner, Ferrer, Forns, & Zanini, ; Manca, Presaghi, & Cerutti, ) and the results of the systematic review by Guerreiro et al. (), who concluded that emotion‐focused and avoidance strategies were consistently linked with self‐harming behavior. The perception of parental support is an important protection factor for NSSI (Baetens et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Escaping problems by smoking, drinking alcohol, being outside the home, sheltering in friendship more than family, and expressing negative feelings by getting angry, yelling, or blaming others were the strategies most reported by adolescents who present R-NSSI. These findings are in agreement with several studies (Kirchner, Ferrer, Forns, & Zanini, 2011;Manca, Presaghi, & Cerutti, 2014) and the results of the systematic review by Guerreiro et al (2013), who concluded that emotion-focused and avoidance strategies were consistently linked with self-harming behavior. The perception of parental support is an important protection factor for NSSI (Baetens et al, 2015).…”
Section: Coping and Nssisupporting
confidence: 92%
“…As expected, avoidance was not a significant moderator. Because the extant literature indicates avoidance is associated with greater levels of NSSI [19], we did not expect avoidance to protect adolescents from the negative impact of poor emotion expression on NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified differences in coping among adolescents who engage in NSSI versus those who do not [17, 18]. Guerreiro and colleagues [19] reviewed the extant literature on coping and adolescent self-injury from 2000 to 2010 and concluded that coping strategies generally deemed “adaptive” (e.g., problem-focused coping, positive reframing, support seeking) are consistently associated with a lower risk of NSSI in adolescents, whereas “maladaptive” coping strategies (e.g., avoidance) are generally linked with higher rates of NSSI [19], although it should be noted that the review did not differentiate suicide attempts from NSSI. Additionally, some mixed findings suggest these links likely differ based on context (e.g., distraction has also proven helpful for self-harmers; [18]).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding such continuum, previous research has demonstrated strong associations between different types of self‐destructive symptoms, namely that suicidal ideation is associated with SA; that a suicide attempt increases the probability of another attempt; that suicidal ideation and NSSI may be associated; and that NSSI behaviors increase the probability of engaging in SA (Spirito et al., ). Although suicidal ideation and NSSI differ regarding their intentionality regarding death, they have similar psychological functions as they both represent inadaptive coping strategies (Guerreiro et al., ; Prinstein, ; Prinstein et al., ).…”
mentioning
confidence: 99%